MENSHIKOVITE, PD3NI2AS3, A NEW PLATINUM-GROUP MINERAL SPECIES FROM TWO LAYERED COMPLEXES, RUSSIA - Barkov A.Y.; Martin R.F.; Pakhomovsky Yakov A.; Tolstykh N.D.; Krivenko A.P. (My University, 2002)
Menshikovite, ideally Pd3Ni2As3 , is a new mineral species found in two localities in Russia. It occurs in a pod of coarse-grained, entirely altered gabbronorite rich in sulfides (up to 30 vol.%), hosted by a microgabbronorite, in the Vostok deposit, Lukkulaisvaara intrusion, in Karelia. There, menshikovite (up to 0.2 mm) is associated with chalcopyrite, pentlandite, calcic amphibole (mostly actinolite), clinochlore, merenskyite, kotulskite, sobolevskite, michenerite, hollingworthite, hessite, and a Re-rich sulfide. Menshikovite (up to 0.1 mm) also occurs in mineralized quartz–feldspar sandstones, which are metasomatically altered and recrystallized. They are located at the lower (exo)-contact of the Chiney intrusion in Siberia, and contain amphibole(s), mica(s), chlorite, disseminated or massive sulfides (mostly chalcopyrite), Pd-rich maucherite, nickeline, sperrylite, mertieite-II or stibiopalladinite (or both), isomertieite, majakite, and michenerite. We also report a third occurrence of menshikovite from the Oktyabr' deposit, Noril'sk complex, in Siberia. In reflected light, menshikovite is pink and opaque. A cleavage is not observed. There is no evidence of bireflectance. The anisotropy is weak, from light gray to brownish gray. Reflectance percentages in air (and in oil) are, for R 1 and R 2 , at 470 nm 48.. Fine twins are present. The average value of microhardness VHN 40, 50, 65 is 517.1 kg/ mm 2 ; it has Mohs hardness of ~5 and is brittle. The average of two sets of multiple wavelength-dispersion electron-microprobe analyses of menshikovite from Lukkulaisvaara gave Pd 48.18, Pt 0.07, Ni 17.77, Fe 0.07, As 33.91, the total is 100.0 wt.% (not normalized), corresponding to Pd 2.99 (Ni 2.00 Fe 0.01) 2.01 As 2.99 (basis: atoms = 8). Compositions of menshikovite from Chiney vary from Pd 3.00 (Ni 1.98 Co 0.01) 1.99 As 2.99 to Pd 3.15 (Ni 1.97 Co 0.01) 1.98 As 2.86 . A solid-solution series probably exists between menshikovite and majakite [i.e., (Pd,Ni) 2 As of the -Pd 2 As type]. The powder pattern of menshikovite from Lukkulaisvaara was indexed on a hexagonal cell with a 8.406(4), c 6.740(4) Å, and V 412.4(6) Å 3 . The strongest eight lines in this pattern [d in Å (I)(hkl)] are 2.626(10)(112), 2.477(10)(202), 2.429(8)(300), 2.283(7)(301), 2.150(6)(103), 1.978(7)(113), 1.818(7)(400) and 1.757(6)(401). Menshikovite formed in volatile-rich environments relatively late in the crystallization history of the layered complexes. The name honors Yurii P. Men'shikov, of the Kola Science Center, Apatity, Russia.
Keywords: menshikovite; new mineral species; Pd–Ni–As system; arsenide; platinum-group mineral; platinum-group elements; layered intrusion; mafic–ultramafic rocks; Lukkulaisvaara; Chiney; Noril’sk; Russia